ANALISIS KINERJA EKONOMI DAN KESEJAHTERAAN MASYARAKAT KABUPATEN MUARA ENIM (KOTA INDUK) DENGAN KOTA PRABUMULIH (KOTA BARU) - Anna Yulianita (Jurnal Ekonomi Pembangunan, 2013)
The title of this research is “The Analysis of some Potencies of the Sectors in Economiy of Muara Enim Regent. It is intended to identify what sectors in the economy of Muara Enim Regent that can be developed during the year 2001 to 2008. The data used in this research is the secondary data from sources. Those data are analysed by using the descriptive and quantitative technic. The quantitative analysis use Location Quetient (LQ) calculation method and Shift Share analysis. The result based on the first method indicates that there are some sectors that can be considered as primary sectors, and this showed by the value of LQ > 1, namely the mining sectors, farm food crops subsector, forestry subsector, electricity subsector, and railways transport subsector. The result based on the Shift Share analysis shows alittle bit different from the first one, where the primary sectors are: the agriculture sectors, the mining sectors, themanufacturing sectors, and the construction sectors, where all its coefficient have positive value. Point elasticity is 5,64 which means that one percent riel sector that had positively effects 5,64 percent on services sector. All those sectors expected to help develop the economy of Muara Enim Regent as a whole. Keyword : Primary sector, Location Quotient, Shift Share, Muara Enim